Determinasi Pertumbuhan Ekonomi di 8 Negara ASEAN - Hafizhy, Muhammad Nadif; Sukarniati, Lestari (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to analyze the factors that influence economic growth in 8 ASEAN countries from 2003 to 2022. The reason for selecting this case study is because ASEAN countries have economic growth rates in the last year reaching an average of 4% -5%. This research uses quantitative methods. Data collection techniques use secondary data sourced from the World Bank. This research was analyzed using the panel data regression method with a fixed effect model approach. The research results show that simultaneously all the independent variables studied (FDI, Trade Openness, Government Expenditures, Exchange Rates, and Inflation) have a significant effect on the dependent variable (Economic Growth). Meanwhile, partially the independent variables that have a significant positive effect are the FDI and Trade Openness variables. The Government Expenditure variable has a significant negative influence. Meanwhile, the exchange rate and inflation variables have a positive but not significant influence.